Femtosecond electron and hole thermalisation in AlGaAs - Bradley, C; Taylor, R; Ryan, J (1989)
Femtosecond optical absorption spectra of AlxGa1-xAs reveal rapid thermalisation of the electron-hole plasma to a two-temperature carrier distribution after ∼ 500fs. The carriers thermalise to a single-temperature distribution at ∼ 10ps. Single phonon emission by electrons is observed at early times when the carrier density is low. Theoretical calculations which model analytically the principal carrier-carrier and carrier-phonon interactions responsible for thermalisation give good agreement with the data. © 1989.